Antimicrobial Properties of Lepidium sativum L. Facilitated Silver Nanoparticles - Samir Haj Bloukh; Zehra Edis; Hamid Abu Sara; Mustafa Ameen Alhamaidah (MDPI AG, 2021)
Antibiotic resistance toward commonly used medicinal drugs is a dangerously growing threat to our existence. Plants are naturally equipped with a spectrum of biomolecules and metabolites with important biological activities. These natural compounds constitute a treasure in the fight against multidrug-resistant microorganisms. The development of plant-based antimicrobials through green synthesis may deliver alternatives to common drugs. Lepidium sativum L. (LS) is widely available throughout the world as a fast-growing herb known as garden cress. LS seed oil is interesting due to its antimicrobial, antioxidant, and anti-inflammatory activities. Nanotechnology offers a plethora of applications in the health sector. Silver nanoparticles (AgNP) are used due to their antimicrobial properties. We combined LS and AgNP to prevent microbial resistance through plant-based synergistic mechanisms within the nanomaterial. AgNP were prepared by a facile one-pot synthesis through plant-biomolecules-induced reduction of silver nitrate via a green method. The phytochemicals in the aqueous LS extract act as reducing, capping, and stabilizing agents of AgNP. The composition of the LS-AgNP biohybrids was confirmed by analytical methods. Antimicrobial testing against 10 reference strains of pathogens exhibited excellent to intermediate antimicrobial activity. The bio-nanohybrid LS-AgNP has potential uses as a broad-spectrum microbicide, disinfectant, and wound care product.